Effects of Standardised Fermented Papaya Gel on Clinical Symptoms, Inflammatory Cytokines, and Nitric Oxide Metabolites in Patients with Chronic Periodontitis: An Open Randomised Clinical Study - Zaira F. Kharaeva; Lyana R. Zhanimova; Magomet Sh. Mustafaev; Chiara De Luca; Wolfgang Mayer; Jeffrey Chung Sheun Thai; Rebecca Tiew Siok Tuan; Liudmila G. Korkina (Hindawi Limited, 2016)
The clinical efficacy of topical administration of standardised fermented papaya gel (SFPG), known to have antioxidant and anti-inflammatory properties, versus conventional therapy was evaluated in a group of 84 patients with moderate-to-severe periodontitis, randomly assigned to control group (n=45) undergoing traditional pharmacologic/surgical protocols or to experimental group (n=39), additionally treated with intragingival pocket SFPG (7 g) applications (15 min daily for 10 days). Patients undergoing SFPG treatment showed significant (P<0.05), durable improvement of three major clinical indices of disease severity: reduced bleeding (day 7), plaque and gingival conditions (day 14), and consistent gingival pocket depth reduction (day 45). Proinflammatory nitric oxide metabolites reached normal values in plasma (day 14) and gingival crevicular fluid (GCF) at day 45 with SFPG applications compared to controls that did not reach normalisation. Levels of highly increased proinflammatory (IL-1B, IL-6) and suppressed anti-inflammatory (IL-10) cytokines normalised in the SFPG group by days 14 (plasma) and 45 (GCF), but never in the control group. Although not acting directly as antibiotic, SFPG acted in synergy with human granulocytes blocking adaptive catalase induction in S. aureus in response to granulocyte-derived oxidative stress, thus enhancing intracellular bacterial killing.